Communication strategies to improve older adults’understanding of health information - Juliana Piveta de Lima; Jamila Geri Tomaschewski Barlem; Daiane Porto Gautério Abreu; Rosemary Silva da Silveira; Marlise Capa Verde Almeida de Mello; Cenir Gonçalves Tier; Silomar Ilha (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to identify communication strategies suggested by Primary Health Care professionals to enhance older adults’ understanding of health information. Methods: this qualitative, exploratory, and descriptive study involved 20 PHC professionals from the Health Units in a city in Rio Grande do Sul. Data were collected in June 2023 through focus groups and analyzed using discursive textual analysis. Results: the category Strategies that Facilitate Communication with Older Adults emerged from the analysis. This category included strategies such as group meetings, using drawings to facilitate understanding, limiting the amount of information provided in each consultation, speaking slowly, using simple language, repeating information, and applying the re-teaching technique. Final Considerations: professionals need training and guidance on communication strategies that can facilitate older adults’ understanding of health information.